Tutela provisória antecedente e a estabilização: uma nova perspectiva para o direito de ação e a supressão de incongruências para garantia da efetividade do processo - Barroso, Darlan (2025)
This thesis examines the preliminary urgent provisional relief and its stabilization techniques, innovative institutes introduced by the 2015 Code of Civil Procedure (CPC/15), which deviate from the traditional model centered exclusively on the exhaustion of cognition and the formation of res judicata. The study proposes a new perspective on the right to action, historically tied to the finality of res judicata, recognizing the autonomy of provisional relief that, through stabilization, can resolve litigations on the factual plane with reasonable effectiveness. The research develops a critical analysis on the evolution of the provisional reliefs in the Brazilian procedural system, emphasizing the influence of foreign models on the formulation of a new model, like the French référé, the Italian provvedimenti d’urgenza, and the inversion of the litigious in the Portuguese civil procedure. The text shows that these models contributed to the redesign of the urgent provisional relief in Brazil, favoring swifter and more adequate mechanisms to the complexity of the contemporary demands. Based on an analytical and propositional approach, the study identifies and seeks to lessen the technical-procedural gaps present in articles 303 and 204 of the CPC/15, which make their full application and practical efficiency difficult, especially regarding the sequence of procedural acts and the exercise of the adversarial. It is sustained that the preliminary provisional relief constitutes an autonomous and bifurcated exercise of the right to action and that the judgment of stabilization represents a third kind of jurisdictional pronouncement, different from the final sentences of merit, or merely terminative. The thesis defends, moreover, the unification of previous procedures to promote more efficiency – even regarding the provisional relief founded on evidence –, and clarifies the nature and effects of stabilization, distinguishing them from the material res judicata. Through interpretive propositions and improvement suggestions, this work seeks to maximize the effectiveness of preliminary action and the efficient installment of jurisdictional relief, while demystifying procedural dogmas to better meet the demands of contemporary justice